Biodegradation of naphthalene by using Pseudomonas sp. and Bacillus sp. / Siti Khairunnisa Mohd Razali - Mohd Razali, Siti Khairunnisa (2016)
Naphthalene is a type of polyaromatic hydrocarbon and is known as the most common pollutant found in our environment. Due to its harmful effects on living things, naphthalene should be removed using the bioremediation method. This method shows us how microorganism can degrade naphthalene by utilizing it as a carbon source. This biodegradation study using Pseudomonas sp. and Bacillus sp. to degrade naphthalene was conducted to analyze the degradation rate of naphthalene, the biomass cell produced and catechol production as well as to compare the degradation activity by those two bacteria species. Both bacteria were cultured separately in M9 minimal media containing naphthalene for 13 days of incubation time. The biodegradation activity of the bacteria cultures were monitored by UV-Vis spectrophotometer. Based on statistical analysis using Pearson’s coefficient of correlation and Mann-Whitney test, Pseudomonas sp. can degrade naphthalene (74.26%) better than Bacillus sp. (71.05%). The biomass cell produced by Pseudomonas sp. was higher (97.32%) than Bacillus sp. (96.09%). Pseudomonas sp. also produced high catechol production (75.31%) than Bacillus sp. (71.06%). This shows that Pseudomonas sp. is more efficient to degrade naphthalene as compared to Bacillus sp. However, both bacteria are capable to degrade naphthalene and are practically useful for bioremediation purposes.